FACTORS INFLUENCING CONSUMER ACCEPTANCE OF MOBILE BANKING AT SAM RATULANGI UNIVERSITY STUDENTS - Massie, Avigayil; Lapian, Joyce S.L.H.V.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Technology has grown in ways we never could have imagined and has an impact on just about every area of our everyday lives. No generation has felt the impact of the technological advances like this generation. New innovations in telecommunications have also had an impact on the banking industry. With equipment that surpass telephone needs, the mobile phone, and later the smartphone has created a lucrative market opportunity, as the number of people owning mobile phones far exceeds any other technological device. This study multiple linear regression analysis, investigated consumer acceptance of mobile banking, case study of bank negara indonesia (bni) with 100 customers of sam ratulangi university students that already used bni mobile banking application. Results indicated that perceived usefulness, perceived ease of use and perceived risk has a significant and positive influence to consumer acceptance of bni mobile banking. From this study the developers should pay attention on these factors when developing a mobile banking service. The developers and managers need to ensure consumers that bni mobile banking services are secure, to reduce the risk for the consumers.Â Keywords: mobile banking, perceived usefulness, perceived ease of use, perceived risk